Estimation of the economic value of the Calakmul Biosphere Reserve, Campeche, Mexico - Hernández Domínguez, Thelma Alicia; Campo Saray, Francisco José Martín del (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2022)
Environmental assets are a source of social, economic and cultural progress in each country, however, they have deteriorated due to human overexploitation and there is widespread concern at the governmental and organizational level in their preservation. Environmental assets provide a variety of goods and services to society, the need to value them as an economic instrument allows to have tangible and monetary elements for adequate conservation plans. The objective of this study was to estimate the economic value of the Calakmul Biosphere Reserve, Campeche, Mexico. It was necessary to analyze factors and indicators of environmental assets of the reserve, study variables that affect the economic value, as well as identify and apply a method for valuation of the reserve. An analysis of institutions and regulations related to the administration, preservation and quantification of environmental assets was presented, where it was identified that there are no specific regulations for the valuation of natural areas as a whole. Regarding the methodological process of valuation of environmental assets, there is no single valuation method, however, the concept of Total Economic Value was applied, which involved direct and indirect uses related to environmental assets, for which, it was necessary to identify benefits that said assets represented and make their economic quantification. Although the value that is concluded with this intervention project is not absolute, it corresponds to a reference value and complies with elements that help to sensitize society in valuing natural resources and compromise the subsistence of future generations.